2009
DOI: 10.1073/pnas.0907564106
|View full text |Cite
|
Sign up to set email alerts
|

Common variants on chromosome 2 and risk of primary open-angle glaucoma in the Afro-Caribbean population of Barbados

Abstract: Primary open-angle glaucoma (POAG) is the second leading cause of blindness worldwide. Although a number of genetic loci have shown association or genetic linkage to monogenic forms of POAG, the identified genes and loci do not appear to have a major role in the common POAG phenotype. We seek to identify genetic loci that appear to be major risk factors for POAG in the Afro-Caribbean population of Barbados, West Indies. We performed linkage analyses in 146 multiplex families ascertained through the Barbados Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 31 publications
3
39
2
Order By: Relevance
“…There was no significant association of either of these two SNPs with HTG and NTG in the present cohort (Tables 1 and 2), and this locus was not associated with POAG in the Japanese population. These two SNPs are common variants in the Japanese population as well as in the Afro-Caribbean population, and the present results indicate that these two SNPs are markers of a neighboring susceptible gene polymorphism responsible for POAG in the Afro-Caribbean population, although Jiao et al (1) reported that they may perform a regulatory role influencing the neighboring gene expression and that, alternatively, one cannot exclude the possibility that they are located within a yet-to-beannotated gene. A variety of genetic factors would contribute to optic neuropathy in POAG.…”
contrasting
confidence: 51%
See 2 more Smart Citations
“…There was no significant association of either of these two SNPs with HTG and NTG in the present cohort (Tables 1 and 2), and this locus was not associated with POAG in the Japanese population. These two SNPs are common variants in the Japanese population as well as in the Afro-Caribbean population, and the present results indicate that these two SNPs are markers of a neighboring susceptible gene polymorphism responsible for POAG in the Afro-Caribbean population, although Jiao et al (1) reported that they may perform a regulatory role influencing the neighboring gene expression and that, alternatively, one cannot exclude the possibility that they are located within a yet-to-beannotated gene. A variety of genetic factors would contribute to optic neuropathy in POAG.…”
contrasting
confidence: 51%
“…Primary open-angle glaucoma (POAG) is the most common form of glaucoma, and it is clinically classified into high-tension glaucoma (HTG), in which an elevated intraocular pressure (IOP) is a major feature, and normal-tension glaucoma (NTG), in which the IOPs are consistently within the statistically normal population range. Jiao et al (1) performed linkage analyses in 146 multiplex families and identified a locus with a major impact on the susceptibility to POAG in the Afro-Caribbean population in Barbados, West Indies. They demonstrated a strong association of rs12994401 and rs1533428 on chromosomes 2p with POAG, according to the findings of subsequent case-control analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We observed no linkage disequilibrium (LD) between the three SNPs in either population based on r 2 (r 2 < 0.35 for all SNP pairs in the respective cases and controls). Although we identified a modest association with POAG risk in the African-American population, risk was conferred by the C allele at rs12994401 rather than the T allele as reported by Jiao et al (1). T allele frequencies in our African-American controls and the Barbados controls were nearly identical.…”
supporting
confidence: 67%
“…There is a correlation between IOP and the likelihood of development of glaucoma and its progression (Boland and Quigley, 2007). Other risk factors are age (Tschumper and Johnson, 1990); family history, ethnicity or genetic variation (Jiao et al, 2009;Rao et al, 2011); other ocular or systemic disease, such as myopia, uveitis, decreased corneal or choroidal thickness, thyroid abnormality, sleep apnea, migraine (Boland and Quigley, 2007;Foster et al, 2002); vacular factors (Yanagi et al, 2011) and others. Age plays an important role in the development of glaucoma.…”
Section: Causes Of Glaucomamentioning
confidence: 99%